Incidence and predictors of new persistent opioid use following inflammatory bowel disease flares treated with oral corticosteroids. Issue 1 (14th November 2018) - Noureldin, Mohamed; Higgins, Peter D. R.; Govani, Shail M.; Cohen‐Mekelburg, Shirley; Kenney, Brooke C.; Stidham, Ryan W.; Waljee, Jennifer F.; Waljee, Akbar K.
Summary: Background: Opioids are commonly prescribed to manage pain associated with inflammatory bowel disease (IBD). It is unknown what percentage of patients develop new persistent opioid use following a steroid‐treated IBD flare. Aim: To identify the incidence and the predictors of new persistent opioid use following an IBD flare. Methods: We used a national insurance claim dataset to identify patients with IBD who received an opioid medication around the time of a corticosteroid‐treated IBD flare. Patients were stratified as previously opioid naïve, intermittent users, or chronic users. The incidence of persistent opioid use among the opioid‐naïve cohort was evaluated along with associated predictors. Results: We identified 15 119 IBD patients who received opioids around the time of a flare. 5411 (35.8%) were opioid‐naïve patients of which 35.0% developed persistent opioid use after the flare. Factors associated with new persistent opioid use include a history of depression (hazard ratio [HR] 1.29, 95% confidence interval [CI] 1.13‐1.47), substance abuse (HR 1.36, 95% CI 1.2‐1.54), chronic obstructive pulmonary disease (COPD) (HR 1.17, 95% CI 1.04‐1.3), as well as, Crohn's disease (HR 1.26, 95% CI 1.14‐1.4) or indeterminate colitis (HR 1.6, 95% CI 1.36‐1.88). Conclusions: New persistent opioid use is common in IBD patients who experience a flare, especially among those with mental health disorders, COPD, and Crohn's disease or indeterminate colitis. These findings can be helpful in risk‐stratifying patients when choosing an acute pain therapy and providing counselling before choosing to prescribe opioids to opioid‐naïve patients experiencing an IBD flare.